2006
DOI: 10.1257/aer.96.5.1802
|View full text |Cite
|
Sign up to set email alerts
|

Did Unilateral Divorce Laws Raise Divorce Rates? A Reconciliation and New Results

Abstract: Applying the Coase Theorem to marital bargaining suggests that shifting from consent to unilateral divorce laws will not affect divorce rates. I show that existing evidence suggesting large effects of divorce laws on divorce rates reflect a failure to explicitly model the dynamic response of divorce rates to a shock to the legal regime. When accounting for these dynamics, I find that unilateral divorce spiked following the adoption of unilateral divorce laws, but that this rise largely reversed itself within a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
385
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 736 publications
(441 citation statements)
references
References 19 publications
(14 reference statements)
16
385
0
3
Order By: Relevance
“…Support for the former claim comes from Kneip and Bauer (2009), who, after examining the impact of unilateral divorce on the divorce rate in a number of Western European countries, found that increased legal rights to unilateral divorce had no long-run effects. In the United States, there was a major expansion of no-fault divorce laws in the 1970s, but this legal change does not seem to have had any lasting effect on the rate of divorce (Wolfers 2006). It might have short-term effects, as couples may adjust the timing of divorce in anticipation of the legal changes, or finally obtain a legal divorce after having lived separately for a longer period of time.…”
Section: National Divorce Legislationmentioning
confidence: 99%
“…Support for the former claim comes from Kneip and Bauer (2009), who, after examining the impact of unilateral divorce on the divorce rate in a number of Western European countries, found that increased legal rights to unilateral divorce had no long-run effects. In the United States, there was a major expansion of no-fault divorce laws in the 1970s, but this legal change does not seem to have had any lasting effect on the rate of divorce (Wolfers 2006). It might have short-term effects, as couples may adjust the timing of divorce in anticipation of the legal changes, or finally obtain a legal divorce after having lived separately for a longer period of time.…”
Section: National Divorce Legislationmentioning
confidence: 99%
“…Flow data have been used extensively by researchers in similar contexts, and they offer several advantages over survey-based measures of marriage and divorce stocks (Bitler et al 2004;Fitzgerald and Ribar 2004;Moffitt and Rendall 1995;Blank 1999;Gittleman 2001;Wolfers 2006). First, CPS and SIPP measures of marriage 9 I omit 1975 and 1976 from the analysis because the data used for the denominator in the marriage and divorce rates (number of unmarried and married women, respectively, ages 15 and over) are drawn from the CPS, which does not have these data available for these years.…”
Section: Empirical Implementationmentioning
confidence: 99%
“…On the other hand, states have also passed no fault divorce laws, which allow partners to seek a divorce without gaining the consent of the spouse. See research by Friedberg (1998) and Wolfers (2006) for an evaluation of the impact of no fault laws on divorce. To examine the robustness of the main results to the choice of lag structure, I experiment with a one-period lag of the EITC.…”
Section: Empirical Modelmentioning
confidence: 99%
“…We also include a dummy variable indicating whether the state uses no-fault for property division and alimony decisions, and a variable that identi es the mandatory separation period required before a no-fault or unilateral divorce is granted; the separation duration variable equals 0 if the state imposes no separation requirement. 12 Both the theoretical and empirical effects of no-fault or unilateral divorce laws on divorce decisions have been debated in the literature for many years (Becker et al 1977;Friedberg 1998;Mechoulan 2006;Peters 1986;Stevenson 2007), with recent ndings (Wolfers 2006) suggesting that the liberalization of divorce law leads to increased divorce rates in the short run.…”
Section: Other Covariatesmentioning
confidence: 99%